BIMBINGAN TEKNIS PENANAMAN HIJAUAN PAKAN TERNAK (HPT) BERBASIS SISTEM TIGA STRATA (STS) PADA PETERNAK KERBAU DI KECAMATAN MOWILA, KONAWE SELATAN - Asminaya, Nur Santy; Nafiu, La Ode; Saili, Takdir; Auza, Fuji Astuty; Abadi, Musram; Agustina, Dian; Gerhana, Gerhana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2025)
The application of a three-strata system (TSS)-based forage planting and processing system has an effect on increasing livestock productivity. This service aims to provide technical guidance to farmers regarding the planting of animal feed forage (AFF) based on the three-strata system. Through this activity, it is expected that farmers can optimise land use, increase forage productivity, and ultimately increase their income. Activities were carried out in 2024 in Wuura Village, Mowila District, South Konawe Regency, in the form of Technical Guidance to the Walaka Mepokoaso Livestock Group. The material provided focuses on AFF planting techniques with a three-strata system approach. The activity stages include preparation of tools and materials, implementation of technical guidance, and evaluation and monitoring. The results of the activity showed that the technical guidance provided effective education to farmers, so that they were able to overcome problems in raising livestock. In addition, the application of the three-strata system has a positive impact on the cultivation of forage.